(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2019)
Background: To report the outcome of hypospadias surgery in authors center and possible ways to achieve an acceptable postoperative outcome. Methods: Total 113 patients were managed in our center of which 108 patients were treated by Snodgrass method. Severe anomalies were managed in staged urethroplasty and buccal graft. Patients were enrolled in two age groups. Post-operative complications as urethrocutaneous fistula, superficial wound infection, meatal stenosis, minor leakage, stricture with diverticulum were experienced and managed. Results: The mean age of the patients of two age groups are 2.5 years & 9.5 years. Post-operative complication were experienced in 30 patients. Nineteen patients developed urethrocutaneous fistula, 10 patients developed meatal stenosis, 3 patients developed stricture with diverticulum and 6 patients were treated conservatively for wound infection and minor leakage. Conclusion: Snodgrass technique is an effective technique for a cosmetically acceptable penis in hypospadias. Although better outcome also depends on operating surgeon’s experience, proper evaluation, per-operative & post-operative supervised management and availability of necessary resources. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 63-65